“We Thought It Would Last Forever”: The Social Scars and Legacy Effects of Mine Closure at Nanisivik, Canada’s First High Arctic Mine - Lim, Tee Wern; Keeling, Arn; Satterfield, Terre (Labour / Le Travail, 2023)
Although mine closures are an inherent feature of extractive industry, they tend to receive less attention in the literature on deindustrialization than the closures of manufacturing and other heavy industries. Until recently, the settler-colonial context of hinterland mineral development and its impact on northern Indigenous lands and communities in Canada have also remained largely unexplored within this literature. Mineral development is historically associated with the introduction of a colonial-capitalist industrial modernity across Canada’s northern regions. Yet the boom-and-bust nature and ultimate ephemerality of mineral development has meant that resource-extractive regions have also been subject to intensive “cyclonic” periods of closure and deindustrialization. This article examines the experience of deindustrialization on the part of the Inuit community of Arctic Bay, who were largely “left behind” by the closure of Nanisivik, Canada’s first High Arctic mine. Through documentary sources and oral history interviews we illustrate how, for Arctic Bay Inuit who were engaged in the cyclonic economies of Nanisivik’s development and closure, there were myriad dimensions of social loss, displacement, and resentment associated with the failure of this industrial enterprise to deliver promised benefits to Inuit, beyond more commonly understood socioeconomic impacts such as job loss.